PENGARUH BRAND IMAGE, GREEN MARKETING MIX DAN STORE ATMOSPHERE TERHADAP MINATA BELI (STUDI PADA KONSUMEN THE BODY SHOP PONTIANAK) - LUMBAN TOBING, Adyttia Dwi Syahlendrha B1021151128 (Jurnal Manajemen Update, 2019)
ABSTRACTÂ This study aims to determine and analyze the influence of Brand Image, Green Marketing Mix, and Store Atmosphere on the buying interest of The Body Shop Pontianak product. This research is quantitative descriptive. The population in the study amounted to 120 respondents who were selected using the purposive sampling method.The results of this study indicate that Brand Image, Green Marketing Mix, and Store Atmosphere have a positive and significant effect on the Interest in Buying The Body Shop Pontianak products. In this study shows that the R2 coefficient value can be 0.641 or 64.1% which means that the influence generated by the variable Brand Image, Green Marketing Mix and Store Atmosphere on Purchase Interest is 64.1% and 35.9% in influenced by other factors.Keywords: Brand Image, Green Marketing Mix, Store Atmosphere, Purchase Interest, The Body Shop, PontianakÂ Â Daftar PustakaÂ Â Agustin, Risna Dwi Dkk. (2015). Pengaruh Green Marketing Terhadap Minat Beli Serta Dampaknya Pada Keputusan Pembelian (Survei Pada Konsumen Non- Member Tupperware Di Kota Malang). Universitas Brawijaya: Malang.Almuarief. (2016). Pengaruh Green Marketing Terhadap Minat Beli Yang Dimediasi Oleh Brand Image. Fakultas Ekonomi, Universitas Negeri Yogyakarta, Yogyakarta.Aydin, S. And Ozer, G. (2005), â€œThe Analysis Of Antecedents Of Customer Loyalty In The Turkish Mobile Telecommunication Marketâ€, European Journal Of Marketing, Vol. 39 Nos 7/8, Pp. 910-25.Berman, Barry dan Evans, Joel. (2004).Retail Manajemen A Strategic Approach.Ninth Edition. New Jersy. Pearson Education Internal.Carrigan, M. And Attalla, A. (2001), â€œThe Myth Of The Ethical Consumer â€“ Do Ethics Matter In Purchase Behaviour?â€, Journal Of Consumer Marketing, Vol. 18 No. 7, Pp. 560-578.Ferdinand, Augusty. (2001). Metode Penelitian Manajemen: Pedoman Penelitian untuk Penulisan Skripsi, Tesis, dan Disertasi Ilmu Manajemen. Semarang: Badan Penerbit Universitas Diponegoro.Ghozali, Imam. (2013). Aplikasi Analisis Multivariate dengan Program SPSS. Semarang. Badan Penerbit Universitas Diponogoro.Hair, Joseph F, William C. Black & Barry J. Babin (2009). Multivariate Data Analysis, 7th Edition. England: Pearson.Hakim, Arif Rachman. (2017). Pengaruh Brand Image Terhadap Minat Beli Konsumen Pada Bimbel Tridaya Bandung. Universitas Telkom: Bandung.Â Â Â Haryadi, Budi. (2009). Pengaruh Strategi Green Marketing Terhadap Pilihan Konsumen Melalui Pendekatan Marketing Mix. Universitas Diponegoro:SemarangHawkins, D.I., dan Mothersbaugh, D.L. (2010) Consumer Behavior: Building Marketing Strategy.11th edition. McGraw-Hill, IrwinJulianti, Ni Luh dkk. (2014). Pengaruh Suasana Toko (Store Atmosphere) Terhadap Minat Beli Konsumen Pada Toserba Nusa Permai di Kecamatan Nusa Penida Tahun 2014. Universitas Pendidikan Ganesha Singaraja: BaliKeller, K. L. (2008). Strategic Brand Manajemen â€“ Building, Measuring and Managing Brand Equity Third Edition. New Jersey: Pearson Education International.Keller, K.L. (1993), â€œConceptualizing, Measuring, And Managing Customer-BasedBrand Equityâ€, Journal Of Marketing, Vol. 57 No. 1, Pp. 1-22.Kotler, P. And Armstrong, G. (2009), Principles Of Marketing, 13th Ed., Pearson, Englewood Cliffs, NJ.Kotler, Philip & Garry Amstrong, (2012). Prinsip-Prinsip Pemasaran.Edisi. 13 JilidJakarta: Erlangga.Kotler, Philip dan Gary Armstrong. (2016). Principle of Marketing (Global Edition). Edisi 16. England: PearsonKotler, Philip.(2005).Manajemen Pemasaran, Edisi Kesebelas, Jilid 2, Edisi Bahasa Indonesia, Jakarta: Penerbit Indeks.Kottler, P. dan Kevin, L. K. (2016). Marketing Managemen (Global Edition), Edisi 15e. England: Pearson.Kuncoro, Mudjarat. (2009). Metode Riset Untuk Bisnis & Ekonomi. Penerbit Erlangga, Jakarta.Lane, W. Ronald, Karen Whitehil King & J. Thomas Russell. (2009). Kleppnerâ€™s: Prosedur Periklanan. Jakarta: PT Index.Lazer, Â W. Â (1969), Â â€œMarketingâ€™s Â Changing Â Social Â Relationshipsâ€, Â Journal Â Of Marketing, Vol. 33 No. 1, Pp. 3-9Levy, Michael, & Weitz, Bortom A. (2001).Retailing Management, Fourth edition, Richard D. Irwin Inc.Â Â Â Malhotra, N. K. (2004). Riset Pemasaran: Pendekatan Terapan. Indeks Kelompok Gramedia: Jakarta.McCarthy, E.J. dan Perrealut, W.D. (2002). Dasar-dasar Pemasaran (terjemahan Agus Darma). Jakarta: Erlangga.Menon, A., Menon, A., Chowdhury, J. And Jankovich, J. (1999), â€œEvolving Paradigm For Environmental Sensitivity In Marketing Programs: A Synthesis Of Theory And Practiceâ€, Journal Of Marketing Theory And Practice, Vol. 7 No. 2, Pp. 1-15Muanaza, Afianka. (2012). Pengaruh Brand Image Terhadap Minat Beli Konsumen (Studi Pada Lion Air Sebagai Low Cost Carrier), Jakarta: Universitas Indonesia.Paul, Temporal & KC. Lee. (2002). High-Tech High-Touch Branding. Terjemahan Anastasia. Jakarta: Selemba empat.Peter, J. Paul & Jerry C. Olson. (1999).Consumer Behavior Prilaku Konsumen dan Strategi Pemasaran, Edisi 4, Jilid 1, Jakarta: Penerbit Erlangga.Polonsky, Michael Jay. (1994). An Introduction To Green Marketing. Electronic Green Journal.Purnama, James. (2014). Pengaruh Produk Ramah Lingkungan, Atribut Merek Hijau, Iklan Peduli Lingkungan dan Persepsi Harga Premium Terhadap Keputusan Pembelian Produk AMDK.Fakultas Ekonomi, Universitas Negeri Yogyakarta, Yogyakarta.Raahmana, Beryanza Tri (2014). Pengaruh Store Atmospehere Terhadap Minat Beli Konsumen Pada UNKL347. Fakultas Bisnis dan Manajemen, Universitas Widyatama, Bandung.Randi. (2016). Pengaruh Citra Merek Terhadap Minat Beli pada Makanan Fast Food Ayam Goreng Texas Chicken Pekanbaru. Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, Risau.Rusdian. (1999). Manajemen Perilaku Konsumen, Jakarta: Salemba Empat. Samuel, Hatane & Adi Suryanata Lianto. (2014). Analisis E-WOM, Brand Image,Band Trust dan Minat Beli Produk Smartphone Di Surabaya. Universitas Kristen Petra: Surabaya.Â Â Â Sangadji, Â Etta Â Mamang Â dan Â Sopiah. Â (2013). Â Perilaku Â Konsumen: Pendekatan Praktisi Disertai Himpunan Jurnal Penelitian. Yogyakarta: C.V Andi Offset. Setiawan, Â Ilham, Â Anton, Â A, Â dan Â Susila, Â I. Â (2004). Â Pengaruh Â Service Â Quality Perception Terhadap Purchase Intention: Studi Empirik Pada KonsumenSupermarket. UsahawanSimamora, B. (2001). Remarketing For Business Recovery â€“ Sebuah Pendekata Riset. Jakarta: PT Pustaka Utama.Sugiyono (2013). Metode Penelitian Kuantitatif, Kualitatif, dan R&D. Bandung: Alfabeta.Sutisna dan Pawitra. (2001) .Perilaku Konsumen dan Komunikasi Pemasaran, Bandung: Penerbit PT. Remaja Rosdakarya.Tjiptono, Fandy. (2011). Manajemen dan Stratejik Merek. Yogyakarta: Penerbit ANDI.Waslito, Jati dan Sujadi. (2014). Model Meningkatkan Niat Pembelian Konsumen Pada Produk Ramah Lingkunagn. Universitas Muhammadiyah Surakarta, Surakarta.Webster, F.E. Jr (1992), â€œThe Changing Role Of Marketing In The Corporationâ€,Journal Of Marketing, Vol. 56 No. 4, Pp. 1-17. www.m.hukumonline.comwww.menlhk.go.id www.pom.go.id www.thebodyshop.co.id Â www.wikipeida.com